Hutang di negara berkembang: Mesin pertumbuhan atau beban ekonomi? - Zakaria, Rinny Apriliany (Journal of Economics Research and Policy Studies, 2025)
Debt remains a primary source of financing for economic development in developing countries. According to data, there was a sharp economic decline and a significant increase in debt levels among developing countries during the COVID-19 pandemic 2019. This indicates a tendency for governments to rely on debt during the recovery period. Theoretically, debt can have either positive or negative impacts on economic development. This implies that debt can serve as a growth engine or become a developmental burden. Amid this debate, this study aims to identify the impact of debt on economic growth in Southeast Asian developing countries (Indonesia, Philippines, Vietnam, and Cambodia) from 2009 to 2022. Using the Autoregressive Distributed Lag (ARDL) method, we find that debt negatively impacts economic growth in both the short and long term. Additionally, another variable, inflation, also negatively affects economic growth in the long term. Therefore, governments must adopt prudent debt management principles and implement strategic policies to ensure that debt is allocated to finance productive sectors.